Interest of Sharia Banking Student IAIN Ternate (Study of Determinants in Choosing a Career in the Banking World) - Nainggolan, Basaria; Soleman, Riky; Hidayat, Nurul Wahida; Marasabessy, Zainal Abidin (Jurnal Ekonomi dan Bisnis Islam (JEBI), 2025)
The aim of this research is to analyze the interest of IAIN Ternate Islamic Banking motivation influences career interest, whether work experience influences career interest, and whether social values influence career interest. Using Holland Theory is a theory that is often used to study and apply for career development. Based on the research results of respondentsstudents (a study that determines when choosing a career in banking) to find out whether work, work motivation influences career interest in sharia banking, work experience does not influence career interest in sharia banking and social values influence career interest in sharia banking